A study of vascular endothelial growth factor in the cord blood of pre-eclamptics and healthy pregnant women - Rawat, Anita; Gangwar, Anil Kumar; Ghildiyal, Archana; Srivastava, Neena; Tiwari, Sunita; Singh, Uma (Asian Journal of Medical Sciences, 2017)
Background: Pre-eclampsia(PE) is the most frequently encountered medical complication during pregnancy. In developing countries PE is a principal cause of maternal mortality. A disturbance in the angiogenic/antiangiogenic factors and in the hypoxia/placental re-oxygenation process, seems to activate a maternal endothelial dysfunction. Aims and Objective: To estimate Vascular Endothelial Growth Factor ( VEGF ) level in the cord blood of healthy and Preeclamptic ( PEc ) pregnant women and to associate this with Preeclamptic pregnancy. Material and Methods: A case-control study ofUmbilical cord serum VEGF levels from women with uncomplicated pregnancies (control group, n=60) and pregnancies complicated by Pre-eclampsia (n=40). VEGF in the cord serum was estimated by SANDWICH Enzyme Linked Immunosorbent Assay method by using ELISA Kit and then compared between the two groups. Results: The mean VEGF concentrations in the women who had pre-eclampsia (578.62±468.3) were lower than in the control group( 625.75±533.1) , but the difference was not statistically significant ( p= 0.8548). Conclusion VEGF plays a key role in the instability between endothelial dysfunction and angiogenesis that occurs during Preeclampsia. VEGF levels might be a useful tool for the early diagnosis of Pre-eclampsia. Asian Journal of Medical Sciences Vol.8(1) 2017 21-25